2021
DOI: 10.1038/s41467-021-25911-x
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in cathode catalyst and cathode layer design for proton exchange membrane fuel cells

Abstract: Proton exchange membrane fuel cells have been recently developed at an increasing pace as clean energy conversion devices for stationary and transport sector applications. High platinum cathode loadings contribute significantly to costs. This is why improved catalyst and support materials as well as catalyst layer design are critically needed. Recent advances in nanotechnologies and material sciences have led to the discoveries of several highly promising families of materials. These include platinum-based all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
114
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 138 publications
(200 reference statements)
0
114
0
Order By: Relevance
“…When FeNi-N 6 was prepared with four N atoms coordinated with the metal atoms, there were fewer H 2 O 2 yields and the four-electron process resulted in better catalytic performance and longer operating life. In the majority of active sites in electrocatalysis, Fe dominated while Ni enhanced the cycling stability [43]. It can be concluded that active sites are very important for electrocatalysis [67].…”
Section: Mofs For Fuel-cell Applications 21 Mofs As Electrode Applica...mentioning
confidence: 98%
See 4 more Smart Citations
“…When FeNi-N 6 was prepared with four N atoms coordinated with the metal atoms, there were fewer H 2 O 2 yields and the four-electron process resulted in better catalytic performance and longer operating life. In the majority of active sites in electrocatalysis, Fe dominated while Ni enhanced the cycling stability [43]. It can be concluded that active sites are very important for electrocatalysis [67].…”
Section: Mofs For Fuel-cell Applications 21 Mofs As Electrode Applica...mentioning
confidence: 98%
“…In order to achieve optimal performance, the proportion of Mn and Zn was adjusted to yield 200 Mn-NC SACs having a life of 1000 h at 0.7 V. Cobalt is another multivalent metal that shows excellent electrocatalytic participation, so the Co-N-C type SACs have also been investigated as catalysts devoid of Fe for H2/O2 fuel cells [78]. By a similar calcination procedure, they were also able to synthesize the Co-N-C catalyst, which behaved similar to the Fe-N-C catalysts and displayed a similar performance to that of the Fe-N-C catalysts owing to the well-distributed CoN4 operating sites, which were afforded by the MOF template [43,62]. In spite of the encouraging catalytic activity of catalysts containing Co-N-C, the presence of agglomerated regions of Co might reduce the intrinsic capabilities of Co and N, which are atomically dispersed within the ZIF-8 precursor, forming a Co-N-C@F127 catalyst after a composition of Plu- As a result of their higher stability and remarkable catalytic activity, other transitionmetal-based catalysts have also been examined in H 2 /O 2 fuel cells.…”
Section: Mofs For Fuel-cell Applications 21 Mofs As Electrode Applica...mentioning
confidence: 99%
See 3 more Smart Citations